2004
DOI: 10.1029/2003wr002120
|View full text |Cite
|
Sign up to set email alerts
|

Lattice‐Boltzmann simulation of two‐phase flow in porous media

Abstract: [1] We simulate two-fluid-phase flow at the pore scale using a lattice Boltzmann (LB) approach. Using a parallel processing version of the Shan-Chen model that we developed, we simulate a set of ideal two-fluid systems and a model two-fluid-phase porous medium system comprised of a synthetic packing with a relatively uniform distribution of spheres. We use the set of ideal two-phase systems to validate the approach and provide parameter information, which we then use to simulate a sphere-pack system. The spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
201
0
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(209 citation statements)
references
References 84 publications
0
201
0
8
Order By: Relevance
“…[37,43,97,98,[197][198][199][200][201][202][203][204][205][206][207], because of its simplicity and easy implementation. Pan et al [197] used the MCMP inter-particle potential model to simulate two-phase flow in a porous medium comprised of a synthetic packing with a relatively uniform distribution of spheres. They achieved good agreement between the measured hysteretic capillary pressure saturation relations and the lattice Boltzmann simulations when comparing entry pressure, displacement slopes, irreducible saturation, and residual entrapment.…”
Section: Inter-particle Potential Modelmentioning
confidence: 99%
“…[37,43,97,98,[197][198][199][200][201][202][203][204][205][206][207], because of its simplicity and easy implementation. Pan et al [197] used the MCMP inter-particle potential model to simulate two-phase flow in a porous medium comprised of a synthetic packing with a relatively uniform distribution of spheres. They achieved good agreement between the measured hysteretic capillary pressure saturation relations and the lattice Boltzmann simulations when comparing entry pressure, displacement slopes, irreducible saturation, and residual entrapment.…”
Section: Inter-particle Potential Modelmentioning
confidence: 99%
“…It was observed that there was a significant dependence of fluid permeability on degree of saturation. However, the used LB model is only available for the liquidgas mixture with a density ratio of less than 58 [17]. The water-gas system whose density ratio is approximately 1000/1.29 = 775 is beyond the capacity of this model.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a prescribed degree of water saturation was simulated by removing a specific amount of water from the large pores in the virtual pore structure of cement paste, which is rather arbitrary and far from accurate, as the distribution of liquid and gas in cement paste at a certain degree of water saturation depends not only on the pore size but also on other microstructural characteristics, e.g., connectivity of pore network and morphology of solid surface [21]. Furthermore, the used LB model in [19] is a single-relaxation-time (SRT) model, which has been proved to be viscosity-dependent, i.e., the dependence of simulation results on the selected relaxation time, an input parameter for LB simulations [17,22].…”
Section: Introductionmentioning
confidence: 99%
“…For the latter, the porosity is exploited in order to trap air with the purpose of achieving better thermal insulation (Dullien, 1992). Soil science is another fruitful research area in the field (Pan, Hilpert, & Miller, 2004;Schaap, Porter, Christensen, & Wildenschild, 2007;Sukop & Or, 2004). In materials engineering, the porosity can also be a key factor in order to meet the highest demands in a variety of applications (Clyne, Golosnoy, Tan, & Markaki, 2006;Furler, Scheffe, Gorbar, et al, 2012;Goodall & Mortensen, 2013;Roberts & Garboczi, 2000;Trimis, Pickenäcker, & Wawrzinek, 2006;Zeschky et al, 2005).…”
Section: Introductionmentioning
confidence: 99%